The Role of Intelligence In Navigating Indonesia’s B40 Biodiesel Policy - Simanjuntak, Bergius Gideon; Permatasari, Diah Ayu; Rika Wijiyanti; Erry S, Hediati; Budi Prasetyono (Journal of Law, Politic and Humanities, 2025)
Indonesia’s 40% biodiesel (B40) mandatory policy, which came into effect in early 2025, represents a strategic initiative to enhance energy security and reduce carbon emissions. However, behind its official objectives, the policy entails significant fiscal, environmental, and social risks that threaten its long-term sustainability. While most analyses have focused on its economic or environmental dimensions, the role of state intelligence in navigating these multidimensional risks remains an underexplored area. This article argues that the success and sustainability of the B40 policy depend not only on technical feasibility or political commitment, but also on the effective application of strategic intelligence functions to provide foresight, mitigate threats, and deliver objective assessments to policymakers, free from partisan and corporate influence. This study adopts a conceptual framework that integrates the intelligence cycle with energy security theory, this article analyses how early detection, early warning, and problem-solving functions can be applied to manage systemic risks such as subsidy traps, feedstock supply deficits, and social tensions. The analysis finds that intelligence plays a crucial role in transforming energy risk management from reactive to proactive. Accordingly, the formal integration of intelligence into the energy policy cycle is a prerequisite to ensure that strategic initiatives such as B40 contribute substantively to sustainable energy, rather than merely serving as economic buffers for entrenched industrial interests.